Turbine design dependency to turbulence: An experimental study of three scaled tidal turbines. (15th August 2021) - Slama, Myriam; Pinon, Grégory; El Hadi, Charifa; Togneri, Michael; Gaurier, Benoît; Germain, Grégory; Facq, Jean-Valéry; Nuño, José; Mansilla, Pablo; Nicolas, Erwann; Marcille, Julie; Pacheco, André
Abstract: In this paper the turbulence effects are studied for three rotors mounted on the same instrumented hub. Two scaled models of industrial turbines and one open-geometry turbine are considered. The turbulence characteristics are obtained from 2D Laser Doppler Velocimeter measurements and the turbine behaviour is analysed from thrust and torque measurements. Three turbulence intensities and a large range of tip speed ratios and flow velocities are considered. The results are anonymised in order to ensure confidentiality. The rotors have different blade profiles, blade numbers and solidity. The rotor design largely modifies the mean power and thrust coefficients. The turbulence intensity only slightly changes these results but has a larger influence on the fluctuating loads than the different rotor designs. The spectral analysis of the rotor torque and thrust shows that, at low frequencies the load variations are correlated to those of the flow velocity with some differences due to the turbulence intensity levels. The coherences between the loads and the velocity seem to be not affected by the rotor type. At high frequencies, the load variations are correlated to the speed control unit of the scaled model and the rotor design has an impact on the rotational speed and loads coherences. Highlights: Load variations are more impacted by the ambient turbulence than the rotor design. Load variations are correlated to the flow velocity fluctuations at low frequency. At high frequencies load fluctuations are only related to the speed control unit.